Review of Books on Student Loans - Avery, Christopher (Journal of Economic Literature, 2019)
This essay reviews three recent books on the causes and consequences of student debt. In addition to increases in college tuition and fees, supply and resource constraints both contribute to the growing phenomenon of default: degree completion rates are relatively low, especially at two-year colleges. Default rates actually decrease with the amount of debt incurred, as students who incur more debt are more likely to complete degrees that bolster their earning power. These books suggest some promising policy options, but there are no quick fixes given that the net cost of attending both private and public colleges continues to rise. (JEL D14, I22, I23, I28)